Treatment of Pediculosis Capitis with Oral Ivermectin - Francisco Purba, William Halomoan; Dalimunthe, Dina A.; Hutapea, Richard (Riviera Publishing, 2025)
Pediculosis capitis is a common scalp infection, especially among school-aged children. It is caused by an infestation of Pediculus humanus var. capitis, a parasite from the Pediculidae family. This case study aims to describe the management of pediculosis capitis using oral Ivermectin. A case study was conducted on a 12-year-old girl with pediculosis capitis, presenting with itching, pain, and burning sensation on the scalp. Dermatological examination revealed the presence of eggs and adult lice. The patient was treated with oral Ivermectin for one week, and evaluation was done using the Scale and SALT Score. After one week of treatment with oral Ivermectin, the patient showed significant improvement. Symptoms of itching decreased, and no live lice were found during follow-up examination. Oral Ivermectin is effective in treating pediculosis capitis with good tolerance. This case study highlights the importance of accurate diagnosis and appropriate treatment in managing pediculosis capitis.